2017
DOI: 10.1016/j.exer.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activity in the meibomian gland: Implications to health and disease

Abstract: The function of the meibomian gland in the upper and lower eyelids is critical to maintaining homeostasis at the ocular surface. Highly specialized meibocytes within the gland must differentiate and accumulate intracellular lipid droplets that are released into the tear film following rupture of the cell membrane. Proteases and their inhibitors have been recognized as key players in remodeling extracellular matrices and promoting the normal integrity of glandular tissue. They modulate a wide range of biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Another important question regarding meibomian glands or MGD involvement in oGVHD is whether pre-conditioning radiotherapy and/or chemotherapy can vaguely destroy its normal quiescent progenitor or stem like cells, depriving the meibomian glands of their ability to replenish lost cells after holocrine secretion [ 31 ]. Studies have shown that rapidly dividing normal cells including, germinal cells and skin cells can be destroyed by chemo- and or radiotherapy [ 31 , 52 ]. The meibomian gland cells undergo fairly rapid process of cell division and has important the commonalities with skin sebaceous therefore its progenitor cells may be lost in a similar manner [ 25 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important question regarding meibomian glands or MGD involvement in oGVHD is whether pre-conditioning radiotherapy and/or chemotherapy can vaguely destroy its normal quiescent progenitor or stem like cells, depriving the meibomian glands of their ability to replenish lost cells after holocrine secretion [ 31 ]. Studies have shown that rapidly dividing normal cells including, germinal cells and skin cells can be destroyed by chemo- and or radiotherapy [ 31 , 52 ]. The meibomian gland cells undergo fairly rapid process of cell division and has important the commonalities with skin sebaceous therefore its progenitor cells may be lost in a similar manner [ 25 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immature meibocytes arise from proliferating basal cells that line the acini and as they divide and differentiate into mature lipid accumulating forms, they move centripetally [ 25 , 29 , 30 ]. At this point, their nuclei become pyknotic and undergo programmed disintegration releasing their content (with ruptured cellular components) into ductules for upward delivery at the ocular surface via the central duct and glandular orifice [ 29 , 30 , 31 ]. Reports suggest that the whole process of meibocyte differentiation and maturation and release of meibum takes averagely 9 days [ 29 , 30 ].…”
Section: Secretory and Postulated Regeneration Properties Of The Mmentioning
confidence: 99%